Kajian Pengaruh Penggunaan Social Network Sites Dalam Mendukung E-Learning Terhadap Motivasi Belajar Siswa - Eva Argarini Pratama - AMIK BSI Purwokerto (Bianglala Informatika, 2016)
Abstract – The social networking site is one of the technological facilities available today, where every day is used / accessed by the thousands and even millions of internet users around the world. This now many social networking sites are also used as e-learning. Some of the advantages of e-learning for e-learning is able to provide flexibility, speed, and interactive visualization through the various advantages of each media one of which is a social networking site. See the advantages of social networking sites and e-learning and the benefits that can be gained not cover the shortage of e-learning, view it then carried out this study to analyze how much influence the use of social network sites as a medium of e-learning on the students motivation , From the results of this analysis showed that No significant effect on the use of social networking sites (socialnetwork sites) against a media e-learning on student motivation, but it is also evident that the diversity of gender, age, and the name of the site that diguanakan, influential on consumer motivation. KataKunci:Social Network Sites, E-learning, Motivasi Belajar